PENGARUH PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DAN KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DESA MAYOA KECAMATAN PAMONA SELATAN KABUPATEN POSO - Usber Purede; Feliks Arfid Guampe; Olvit Olniwati Kayupa (Jurnal Kebijakan Pembangunan Daerah, 2025)
Infrastructure limitations and low community participation have resulted in suboptimal public service quality and citizen satisfaction in Mayoa, Poso. This study aims to examine the influence of community participation in development and the quality of public services on community satisfaction in Mayoa Village, South Pamona Subdistrict, Poso Regency. The selection of Mayoa Village as the research location is based on its characteristics as a rural area with strong community participation dynamics and ongoing challenges in public service delivery. The relevance of this topic is significant in the context of rural development, as community participation is a key to achieving inclusive development, while the quality of public services reflects the effectiveness of village governance. This research uses a quantitative approach with a survey method. A purposive sampling technique was employed to select 41 respondents from 743 households in Mayoa Village. The sample size calculation considered the representation of community members actively involved in development and direct users of public services. Data were collected using questionnaires and analyzed through multiple linear regression. The results show that both community participation and the quality of public services have a significant effect on community satisfaction, both partially and simultaneously. These findings have practical implications for the formulation of village development policies and provide theoretical contributions to the literature on the relationship between participation, public services, and community satisfaction in rural areas.